PELATIHAN DAN PEMBERIAN BANTUAN ALAT KESEHATAN SERTA MINI GARDEN PORTABLE BAGI POSYANDU REMAJA MOJO - Purbowati, Rini; Hernanda, Pratika Yuhyi; Isrianto, Pramita Laksitarahmi; Tjandra, Lusiani; Masfufatun, Masfufatun; Aritania, Putu Oky; Indahsari, Noer Kumala (UNIVERSITAS PGRI MADIUN, 2024)
Abstract. The increase in non-communicable diseases (NCDs) that occur at young and productive ages is triggered by the tendency of teenagers to like to consume